Math, asked by urvitjajoo123, 1 year ago

Factorise x
x {}^{3}  + 2x {}^{2}  - 5x - 6
+ 2x2 - 5x - 6.​

Answers

Answered by sudiplal22
0

Answer:

the correct answer is (x-2)(x+3)(x+1)

Step-by-step explanation:

x^{3} +2x^{2} -5*x-6\\

let x=2

2^{3} +2*2^{2} -5*2-6 = f(2)

8+2*4-10-6 = f(2)

8+8-16 = f(2)

16-16 =f(2)

0= f(2)

therefore  x-2 is a factor

now divide ( x^{3} +2x^{2} -5*x-6) by (x-2)

then by dividing we get \\x^{2} +4*x+3

on complete factorisation we get (x-2)(x+3)(x+1)

Similar questions